Wild hearts : contemporary lesbian melodrama - Benton, Mary; Dunhill, Christina; Gapper, Frances; Rimsk, Tara; Sandler, Helen (London : Sheba Feminist Press, 1991)
Fonds Suzan Daniel (FSD)
Engels
Monografie